P51 Tuberculosis outcome following pre-treatment assessment for directly observed or self-administered therapy: still room for improvement?. (2nd December 2011) - Barrett, J C; Dart, S; Solamalai, A; Snook, C; Lipman, M
Abstract : Setting and Methods: London has high rates and large numbers of TB notifications. Treatment completion is generally <85% (the figure recommended by the WHO to achieve effective control). NICE TB guidelines (2011) advise using risk assessment to identify those individuals most likely to non-adhere to therapy and hence who require enhanced case management, including directly observed therapy (DOT), to complete treatment successfully. The North Central London TB Network piloted a risk assessment tool, derived from reported risk factors predisposing to non-adherence plus information from a patient profile study undertaken across London, in a cohort of 306 TB patients starting treatment between June and December 2008. On the basis of the individual's risk of non-adherence score they were broadly allocated to DOT or self-administered therapy (SAT). Here we evaluate treatment outcomes (completion and need for re-treatment) using the London TB register (LTBR) and individual case records. Results: Subjects receiving SAT had excellent treatment completion rates (91%), with 3% lost to TB service follow-up (Abstract P51 table 1 ). Those on DOT had a lower completion rate—which at 80% was less than the international standard. Ten per cent of DOT subjects were lost to follow-up (all after transfer out of NCL TB service care). Death rates were threefold higher in the DOT group. After 20 months median follow-up post treatment completion, 3 SAT and 0 DOT patients had been re-treated for TB. Conclusions: The risk assessment tool appears to discriminate those patients who can receive SAT; though it should be noted that re-treatment was only required in this group—suggesting possible poor adherence with therapy in some individuals. Subjects on DOT did well within NCL TB service, but were too often lost to follow-up if transferred elsewhere. It is unclear whether this reflects inadequate local data collection and communication by, and with, our service, or genuine loss from healthcare. Either way, this requires urgent attention. The planned introduction of enhanced case management within the London TB model of care may improve this.